Trowaglerix Venom Polypeptides As a Novel Antithrombotic Agent by Targeting Immunoglobulin-Like Domains of Glycoprotein VI in Platelet. Issue 7 (July 2017) - Chang, Chien-Hsin; Chung, Ching-Hu; Tu, Yi-Shu; Tsai, Cheng-Chieh; Hsu, Chun-Chieh; Peng, Hui-Chin; Tseng, Yufeng J.; Huang, Tur-Fu
Abstract : Objective—: Currently prescribed antiplatelet drugs have 1 common side effect—an increased risk of hemorrhage and thrombocytopenia. On the contrary, bleeding defects associated with glycoprotein VI (GPVI) expression deficiency are usually slightly prolonged bleeding times. However, GPVI antagonists are lacking in clinic. Approach and Results—: Using reverse-phase high-performance liquid chromatography and sequencing, we revealed the partial sequence of trowaglerix α subunit, a potent specific GPVI-targeting snaclec (snake venom C-type lectin protein). Hexapeptide (Troα6 [trowaglerix a chain hexapeptide, CKWMNV]) and decapeptide (Troα10) derived from trowaglerix specifically inhibited collagen-induced platelet aggregation through blocking platelet GPVI receptor. Computational peptide design helped to design a series of Troα6/Troα10 peptides. Protein docking studies on these decapeptides and GPVI suggest that Troα10 was bound at the lower surface of D1 domain and outer surface of D2 domain, which was at the different place of the collagen-binding site and the scFv (single-chain variable fragment) D2-binding site. The newly discovered site was confirmed by inhibitory effects of polyclonal antibodies on collagen-induced platelet aggregation. This indicates that D2 domain of GPVI is a novel and important binding epitope on GPVI-mediated platelet aggregation. Troα6/Troα10 displayed prominent inhibitory effect of thrombus formation in fluorescein sodium-induced platelet thrombus formation of mesenteric venules and ferric chloride-induced carotid artery injury thrombosis model without prolonging the in vivo bleeding time. Conclusions—: We develop a novel antithrombotic peptides derived from trowaglerix that acts through GPVI antagonism with greater safety—no severe bleeding. The binding epitope of polypeptides on GPVI is novel and important. These hexa/decapeptides have therapeutic potential for developing ideal small-mass GPVI antagonists for arterial thrombogenic diseases. Abstract : Supplemental Digital Content is available in the text.